2020
DOI: 10.2147/pgpm.s265121
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prognostic Values of Radiosensitivity Genes and CD19 Status in Gastric Cancer: A Retrospective Study Using TCGA Database</p>

Abstract: Background The correlation between the radiosensitivity genes combined with CD19 status and clinical outcome was investigated to identify gastric cancer (GC) patients who would benefit from radiotherapy combined with CAR-T cell therapy. Methods The gene expression and clinical features were downloaded from The Cancer Genome Atlas (TCGA) Stomach Cancer (STAD). To identify the hub radiosensitivity genes and CD19 status, 407 patients were categorized into two groups: radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Nevertheless, these studies collectively con rmed that NPC patients with high CD19 + B lymphocytes had a better survival rate. In addition, previous studies have reported that B lymphocytes are associated with better survival when observed in gastric cancer and head and neck cancer (Liang et al 2020;Pretscher et al 2009;Yu et al 2012).…”
Section: Discussionmentioning
confidence: 94%
“…Nevertheless, these studies collectively con rmed that NPC patients with high CD19 + B lymphocytes had a better survival rate. In addition, previous studies have reported that B lymphocytes are associated with better survival when observed in gastric cancer and head and neck cancer (Liang et al 2020;Pretscher et al 2009;Yu et al 2012).…”
Section: Discussionmentioning
confidence: 94%
“…For example, Capnocytophaga and Helicobacter were only found in the ESCA and STAD cohorts. It is known that Helicobacter pylori is a major etiological factor in the development of upper GI tract conditions (34), and its infection in the stomach is a risk factor for STAD prognosis (35). On the contrary, Faecalibacterium was found only in CRC samples.…”
Section: Several Studies Have Recently Characterized the Profile Of Tissue-mentioning
confidence: 99%
“… 2 , 3 Though some risk factors for STAD have been established, the molecular mechanism of the occurrence and progression of STAD is still far from clear. 4 Moreover, the therapeutic measures for STAD are limited and the prognosis for STAD patients are poor, with the overall survival rate of STAD patients in advanced stage of only approximately 12 months. 5 These alarming data suggested the urgent need of new prognostic biomarkers and therapeutic targets for STAD patients.…”
Section: Introductionmentioning
confidence: 99%